Computational fluid dynamic model of nonisothermal circulating fluidized bed riser for CO2 capture. (December 2020) - Sornvichai, Amolwan; Piemjaiswang, Ratchanon; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon
Abstract: The concern about the environment is the driving force to reduce the CO 2 emission. The main source of CO2 emission is from the flue gas from combustion process. The K 2 CO 3 solid sorbent in circulating fluidized bed reactor (CFB) is nominated as an efficient method for capturing CO 2 in flue gas. The CFB reactor consists of two reactors including circulating fluidized bed riser (CFBR) and circulating fluidized bed downer (CFBD). The study focused on the CFBR as it was used in adsorption process. However, CO2 capture capacity is limited due to the equilibrium at the specific system temperature. This study developed the computational fluid dynamics model of the nonisothermal circulating fluidized bed riser which included effect of the cooling water tube. The simulation procedure found the suitable grid number and simulation time of 420, 000 cells and 100 s, respectively. The effect of cooling water temperature on the system hydrodynamics and temperature profiles was investigated. The results showed that the CO2 capture capacity increases with the decreasing temperature of cooling water temperature.